Optimizing MR Imaging Detection of Type 2 Focal Cortical Dysplasia: Best Criteria for Clinical Practice - Mellerio, C.; Labeyrie, M.-A.; Chassoux, F.; Daumas-Duport, C.; Landre, E.; Turak, B.; Roux, F.-X.; Meder, J.-F.; Devaux, B.; Oppenheim, C. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: Type 2 FCD is one of the main causes of drug-resistant partial epilepsy. Its detection by MR imaging has greatly improved surgical outcomes, but it often remains overlooked. Our objective was to determine the prevalence of typical MR imaging criteria for type 2 FCD, to provide a precise MR imaging pattern, and to optimize its detection. MATERIALS AND METHODS: We retrospectively reviewed 1.5T MR imaging of 71 consecutive patients with histologically proved type 2 FCD. The protocol included millimetric 3D T1-weighted, 2D coronal and axial T2-weighted, and 2D or 3D FLAIR images. Two experienced neuroradiologists looked for 6 criteria: cortex thickening, cortical and subcortical signal changes, blurring of the GWM interface, the “transmantle” sign, and gyral abnormalities. The frequency of each sign and their combination were assessed. We compared the delay between epilepsy onset and surgery, taking into account the time of type 2 FCD detection by MR imaging. RESULTS: Only 42 patients (59%) had positive MR imaging findings. In this group, a combination of at least 3 criteria was always found. Subcortical signal changes were constant. Three characteristic signs (cortical thickening, GWM blurring, and transmantle sign) were combined in 64% of patients, indicating that MR imaging can be highly suggestive. However, typical features of type 2 FCD were overlooked on initial imaging in 40% of patients, contributing to a delay in referral for surgical consideration (17 versus 11.5 years when initial MR imaging findings were positive). CONCLUSIONS: A combination of 3 major MR imaging signs allows type 2 FCD to be recognized in clinical practice, thereby enabling early identification of candidates for surgery. EEGelectroencephalography18FDGfluorine 18 FDGGWMgray-white mattertype 2 FCDtype 2 focal cortical dysplasia